The effect of HPV analysis on the ASC/SIL ratio which is one of the quality control criteria for PAP smears - ERBARUT SEVEN, İPEK (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: The high number of smear tests has a workload on pathologists/cytopathologists, which raises the concern for the quality of diagnoses. The application of high-risk human papillonfavirus (hr-HPV) analyses with the PAP smear has begun to contribute to the clinical practice. In this study, we aimed to show the effect of hr-HPV analysis on the results of PAP smear via atypical squamous cell/squamous intraepithelial lesion (ASC/SIL) ratio on the quality standards. Materials and Methods: A total of 12799 cervical cytology reports, between 2014-2016, from the Pathology Department of Marmara University Hospital, were included. Between November 2014 and May 2016, hr-HPV analysis was performed on a total of 4307 cases with Hologic Aptima HPV (TM), USA. Smear diagnoses before and after the start of the HPV test application were recorded. Results: The cytology diagnoses, during when hr-HPV screening was not performed, were negative for intraepithelial lesion or malignancy (NILM) 99.4%, atypical squamous cells of undetermined significance (ASCUS) 0.6%, low-grade squamous intraepithelial lesion (LSIL) 0.2%, ASC-H 0.04%, and high-grade squamous intraepithelial lesion (HSIL) 0.13%. The cytology diagnoses that were evaluated with HPV test were as follows: NILM 93.67%, ASCUS 2.31%, LSIL 2.82%, ASC-H 0.3%, and HSIL 0.91%. ASC/SIL ratio has been dropped from 1.9 to 0.7 after the initiation of hr-HPV use. Conclusion: During the period without hr-HPV analysis, the ASC/SIL ratio was 1.9. Later with the initiation of hr-HPV screening this ratio decreased to 0.7. This shows that knowing HPV test results affects and improves the quality of the laboratory diagnoses.
Keywords: ASC/SIL; ratio; Quality; PAP smear; HPV analysis; CYTOLOGY